2022
DOI: 10.1155/2022/5482895
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] The Comparative Pharmaco‐ and Histokinetics of the Therapeutic Dose of Estradiol Valerate and Bromocriptine in Common Quails

Abstract: The current study is aimed at examining the overall effects of steroids on the tissues of organisms and pharmacotherapeutics and pharmaco-histokinetics of several steroids, including Bromocriptine as mesylate and estradiol valerate in common quails (Coturnix coturnix). A total of 100 birds were used for pharmaco-histokinetics. The research was carried out in two separate trials, one during the fall season and the other during the spring season. Each experiment lasted for five, ten, fifteen, and twenty days. Ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%